Upper Gastrointestinal Endoscopy as Diagnostic Test for Detection of Gastric Malignancy in Sanglah Hospital Denpasar - Hendra Koncoro; Putu Prathiwi Primadharsini; Luh Putulin Indrayani; I Dewa Nyoman Wibawa (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Gastric malignancy is the third most common cause of cancer-related death in the world. Upper gastrointestinal (UGI) endoscopy for detection of gastric malignancy has been used widely in Indonesia. This study aimed to determine the prevalence of gastric malignancy and diagnostic value of UGI endoscopy in detection of gastric malignancy in Sanglah Hospital, Denpasar.Method: A retrospective study on patients undergoing UGI endoscopy in Endoscopy Unit of Sanglah Hospital Denpasar between January 2012 and December 2014 was conducted. Endoscopical and histological diagnosis were documented. The diagnostic test of endoscopic diagnosis were conducted by showing its sensitivity, specificity, positive predictive value, negative predictive value, and accuracy.Results: One thousand and sixty eight patients with upper gastrointestinal symptoms were subjected to endoscopy between January 2012 and December 2014. Of the 1068 cases, 39 patients were suspected for gastric malignant lesions on UGI endoscopy. During the study period, histopathologically-confirmed gastric malignancy was found in 2.72% patients. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of UGI endoscopic diagnosis for these neoplastic lesions were 100%, 99.04%, 74.36%, 100%, and 99.06%, respectively.Conclusion: The prevalence of gastric malignancy was higher compared to western countries. Endoscopy is important as diagnostic tool in patients with suspicion of gastric malignancy. Greater suspicion in clinical judgment and carefulness in excluding malignancy through one histopathology negative findings need to be done to reduce the number of misdiagnoses of gastric malignancy.